How is forest landscape restoration being Implemented in Burkina Faso? Overview of ongoing initiatives - Vinceti, Barbara; Valette, Michel; Bougma, Ali Lardia; Turillazzi, Arturo (MDPI, 2020)
Land degradation affects a significant portion of the Earth’s ice-free land area and several countries have embraced the challenge of restoring large parts of their degraded lands. Success in these efforts depends on various factors, including the amount of resources invested, the technical capacity available and the degree of involvement of stakeholders. Burkina Faso has committed to restoring 5 Mha of degraded land by 2030. We identified 39 forest landscape restoration initiatives (FLR) in this country and interviewed their managers to obtain an overview of critical aspects and constraints that could orient future efforts. Our results show a recent growth of FLR initiatives, as most of the projects examined started in the last few years; however, the scale of implementation seems incompatible with country-level targets. Funding is coming mainly from international cooperation and this may lead to risks in long-term continuity and sustainability of FLR. Furthermore, FLR projects are carried out by a multitude of agencies, with local NGOs and associations as the main players; this finding highlights the need to coordinate ongoing efforts and flag challenges in tracking progress. Tree planting is common to most FLR initiatives examined, with aspects of quality and quantity of planting material available becoming critical in ensuring success; this raises the need to ensure farmers are well-trained in its collection and handling. Finally, more homogeneous approaches in monitoring across FLR initiatives should be adopted